ASPIRING PANGANDARAN GEOPARK TO PROMOTE SUSTAINABLE TOURISM DEVELOPMENT - Rifki Rahmanda Putra; Eka Susanto; Raden Willy Ananta Permadi; Muhammad Iqbal Maulana; Moh Sapari Dwi Hadian; Heryadi Rachmat; Shandra Rama Panji Wulung (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Abstract Purpose: the main focus in this research is to identify and map geological and non-geological potentials based on three main pillars in the development of geoparks, namely geodiversity, biodiversity and cultural diversity Research methods: The method used in this research is qualitative research with a case study design. While the analysis techniques used are interactive models and map analysis, using Arcgis 10.3. Results and discussions: The results showed that in addition to geological sites, many non-geological sites can be developed into geotourism attractions with high cultural and biodiversity values. Conclusion: Geotourism in Pangandaran Regency has enormous potential which is the basis for the formation of the Aspiring Geopark Pangandaran with the principle of sustainable development. Keywords: aspiring geopark, geotourism, geopark, Pangandaran Regency, sustainable tourism